Corrosion resistance of AlN-based ceramics to molten uranium. Issue 7 (1st April 2022) - Wang, Zhongyan; Cai, Shu; Luo, Liping; Wang, Dingding; Zuo, You; Ling, Lei; Liu, Pengbo; Tian, Meng; Lv, Xuming
Abstract: A kind of AlN-based ceramics was prepared as a lining material of the high-density graphite crucible for high temperature melting uranium. During the corrosion experiment, the corrosion rate showed a downward trend with the increase of corrosion time. As the corrosion time increased from 2 h to 8 h, the corrosion rate showed a gradual downward trend from 0.25 mg cm −2 h −1 to 0.22 mg cm −2 h −1, and then decreased significantly to 0.07 mg cm −2 h −1 at 16 h. A dense layer consisting of UO2, Y2 O3 and UC was formed between molten uranium and AlN-based ceramics, and the thickness increased with the extension of corrosion time, resulting in a significant decrease in corrosion rate.